2008
DOI: 10.1073/pnas.0807235105
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic surfaces for enhanced differentiation of embryonic stem cell-derived embryoid bodies

Abstract: With their unique ability to differentiate into all cell types, embryonic stem (ES) cells hold great therapeutic promise. To improve the efficiency of embryoid body (EB)-mediated ES cell differentiation, we studied murine EBs on the basis of their size and found that EBs with an intermediate size (diameter 100 -300 m) are the most proliferative, hold the greatest differentiation potential, and have the lowest rate of cell death. In an attempt to promote the formation of this subpopulation, we surveyed several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 37 publications
(44 reference statements)
7
122
0
Order By: Relevance
“…3D), while at high cell densities the EB size is primarily between 100 and 300 mm, which has been previously reported to have increased differentiation into various lineages. 53 Additionally, higher rotation speeds demonstrate a trend of an increased number of smaller EBs compared to lower rotation speeds (Fig. 3E).…”
Section: Fridley Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…3D), while at high cell densities the EB size is primarily between 100 and 300 mm, which has been previously reported to have increased differentiation into various lineages. 53 Additionally, higher rotation speeds demonstrate a trend of an increased number of smaller EBs compared to lower rotation speeds (Fig. 3E).…”
Section: Fridley Et Almentioning
confidence: 99%
“…3E). Although EB size has been shown to a significant factor in stem cell fate, 53 the flow cytometry data were collected with the same variations in cell seeding density and rotation speeds so that the trends in differentiation are regardless of EB size. We have demonstrated that EB size alone is not the defining factor in ES cell hematopoiesis; even if size differences are not significant, parameters like rotation speed and cell seeding density can have significant influence on differentiation.…”
Section: Fridley Et Almentioning
confidence: 99%
“…Nonetheless, ROCKi is a xeno-factor and has been shown to bias cell fate toward residual pluripotency and inhibit differentiation in neural differentiation studies, reducing the utility of the derived cells for potential clinical applications [30]. To facilitate cell aggregation in suspension for EB formation, nonadhesive culture surfaces were developed [12,31], and soluble factors that promote cell-cell interactions were administered in the culture media [32]. Recently, a serum-free, animal product-free defined medium, mTeSR TM 1, has been developed to support the feeder-independent culture and EB formation from dissociated hESCs [33,34], making it possible to derive clinically relevant human cell lineages from hPSCs in a reproducible manner.…”
Section: Conventional Methodsmentioning
confidence: 99%
“…Elsewhere, plasma-deposited gradients of octadiene to acrylic acid were fabricated to investigate the effect of carboxylic group (COOH) concentration on mouse ES cell adhesivity and differentiation status (Wells et al, 2009). In addition, by altering the hydrophobicity of a surface, the formation and differentiation potential of ES cells within embryoid bodies (EBs) can be tuned to promote a desirable EB size and composition (Valamehr et al, 2008).…”
Section: Surface-based Control Of the Morphology And Function Of Cultmentioning
confidence: 99%